Nanostructural characteristics of polymer adsorption layers formed under ultrasonic treatment on metal oxides surface in aqueous dispersions - Bulychev, Nikolay; Kisterev, Edward; Ioni, Yulia; Dirnberger, Klaus; Zubov, Vitali; Eisenbach, Claus (Publishing House of Lviv Polytechnic National University, 2011)
The course and the result of the surface modification of titanium dioxide and ferrous oxide pigments in aqueous dispersion by ethylhydroxyethylcellulose (EHEC) without and with mechanical treatment of the dispersion by ultrasonic power was studied by the electrokinetic sonic amplitude (ESA) method. The evaluation of the ESA data showed that the ultrasonic treatment causes a significant thickness increase of the EHEC layer on the pigment which is primarily attributed to the ultrasonically induced activation of the pigment surface. The thickness of the polymer adsorption layer derived from ESA measurements was confirmed by TEM investigations. The ultrasonic treatment leads to significant changes of the adsorption layers properties and is a promising method for the surface modification of pigments with regard to dispersion stability. За допомогою електрокінетичної звукової амплітуди (ЕЗА) досліджено процес модифікації поверхні пігментів діоксиду титану та оксиду заліза у водних дисперсних системах при введенні етилгідроксиетилцелюлози (ЕГЕЦ) у відсутності та в присутності механічного оброблення дисперсних систем ультразвуком. Інтерпретацією даних ЕЗА показано, що ультразвукове оброблення викликає суттєве збільшення товщини шару ЕГЕЦ на поверхні пігментів, що пояснюється ультразвуковою активацією поверхні. Дані про товщину шарів, oтримані методом ЕЗА, підтверджені дослідженнями з використанням просвічуючої електронної мікроскопії. Ультразвукове оброблення призводить до значних змін характеристик адсорбційних шарів і є перспективним методом для модифікування поверхні пігментів та підвищення стабільності дисперсних систем.
Наноструктурні характеристики полімерних адсорбційних шарів, утворених на поверхні оксидів металів у водних дисперсних системах під дією ультразвуку
Keywords: aqueous dispersions; polymers; electrokinetic sonic amplitude method; polymer adsorption layers; водні дисперсні системи; полімери; метод електрокінетичної звукової амплітуди; полімерні адсорбційні шари; ультразвукове оброблення; ultrasonic treatment